2009
DOI: 10.4317/medoral.14.e563
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Cell Proliferation Ratio in Oral Lichen Planus, Epithelial Dysplasia and Oral Squamous Cell Carcinoma

Abstract: http://www.medicinaoral.com/medoralfree01/v14i11/medoralv14i11p563.pdf AbstractBackground: Although oral lichen planus has been classified by the World Health Organization (WHO) as a potentially malignant disorder, such classification is still the target of much controversy. Aim: To evaluate the cell proliferation rate in oral lichen planus, comparing it to the rate observed in epithelial dysplasia and oral squamous cell carcinoma, aiming at indications which might indicate the potential for malignant transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
3
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 17 publications
2
25
3
4
Order By: Relevance
“…In this study, Ki67LI in group B was less than that of in group C, which might indicate less growth potential in OLP lesions, possibly indicating a lower aggregation of genetic mutations compared to dysplastic lesions (de Sousa et al, 2009b). On the other hand, there was no significant difference between OLP and epithelial dysplasia indicating an equal potential for these two groups to develop malignancy.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…In this study, Ki67LI in group B was less than that of in group C, which might indicate less growth potential in OLP lesions, possibly indicating a lower aggregation of genetic mutations compared to dysplastic lesions (de Sousa et al, 2009b). On the other hand, there was no significant difference between OLP and epithelial dysplasia indicating an equal potential for these two groups to develop malignancy.…”
Section: Discussioncontrasting
confidence: 58%
“…In another study by de Sousa et al (2009b), evaluation of cell proliferation in OSCC, dysplastic and OLP cases showed significant difference between OLP and OSCC . However, there was no significant difference between OLP and epithelial dysplasia (de Sousa et al, 2009b), which was similar to those of the present study regardless of the evaluation methods and cell proliferation markers applied.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Buajeeb et al (16) have reported that p16 is not reliable for oral mucosal dysplasia and malignant transformation, although it is possible that p16 plays a role in cell senescence in normal oral mucosa since the protein is detectable by Western blotting in normal oral mucosa (3). Sousa et al (17) have reported that no significant statistical difference of the cell proliferation rate between oral lichen planus and epithelial dysplasia (p>0.05) and between the epithelial dysplasia and oral squamous cell carcinoma (p>0.05) was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Oral biopsy with a histopathological evaluation is necessary to validate the clinical diagnosis of LP. Most importantly, LP can develop into an oral squamous cell carcinoma [8,9]. There are several long-term prospective studies that show a malignant transformation rate of 4.0% [10,11].…”
mentioning
confidence: 99%